Food Safety Temperature Monitoring At The Montage Big Sky Hotel In The United States - I Made Artha Kusuma Jaya; Ni Luh Supartini (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
This study aims to determine the influence of temperature control in the pizza-making process and to understand the storage management mechanisms for raw materials and cooked materials in the kitchen of the Montage Big Sky Hotel, United States. Temperature control is a crucial factor in modern food safety systems as one of the Critical Control Points (CCP) based on the principles of Hazard Analysis and Critical Control Points (HACCP) to prevent the growth of pathogenic microorganisms and cross-contamination. Using a descriptive qualitative approach through participatory observation during an internship period, the researcher directly observed daily kitchen operational procedures. Data collection was also supported by semi-structured interviews with the Chef de Cuisine, Sous Chef, and kitchen staff, alongside temperature log documentation. The results indicate that the Montage Big Sky kitchen has implemented a structured and sustainable temperature control system. Daily temperature monitoring is consistently conducted for chiller and freezer facilities utilizing temperature log sheets. In the pizza-making process, dough fermentation temperature is strictly controlled to maintain yeast activity stability, while baking is performed at an adequate high temperature to ensure the destruction of pathogenic microorganisms. Furthermore, the storage of raw and cooked materials is separated using closed containers and systematic shelf arrangements. Overall, the field implementation aligns with standard operating procedures (SOP) and HACCP principles, though staff discipline and consistent managerial supervision remain essential to maintain service quality and food safety for hotel guests.